EXPLORING THE ROLE OF AI TOOLS IN SUPPORTING SELF-REGULATED LEARNING AMONG HIGH-USAGE EFL STUDENTS - Sandy Sandy; Farouk Imam Arrasyid; Siti Luruh Ayu Noerjanah (UIN Siber Syekh Nurjati Cirebon, 2026)
Artificial Intelligence (AI) tools have increasingly become part of English as a Foreign Language (EFL) students’ learning practices, offering immediate support for understanding materials, completing academic tasks, and managing independent study. However, the lived experiences of high-usage EFL students in using AI tools to support self-regulated learning remain underexplored, particularly in Indonesian Islamic university contexts. This study explored the roles of AI tools in supporting self-regulated learning, students’ experiences and perceptions, and the problems and solutions related to AI-accelerated learning in EFL education. Using a qualitative transcendental phenomenological design, data were collected from five high-usage EFL students at UIN Siber Syekh Nurjati Cirebon through semi-structured in-depth interviews and digital artifacts. The data were analyzed using Moustakas’ phenomenological analysis. The findings showed that AI tools helped students understand English materials, plan learning strategies, monitor progress, evaluate learning outcomes, develop language skills, and maintain motivation. Students perceived AI as a flexible learning partner, yet they also faced inaccurate responses, overdependence, reduced critical thinking, and difficulties in using AI feedback. The study concludes that AI tools can support self-regulated learning when used responsibly as learning assistance rather than as a replacement for students’ personal effort.